IMPLEMENTASI FINITE STATE AUTOMATA UNTUK OPTIMALISASI PROSES DISTRIBUSI DAUR ULANG SAMPAH - Tyas Nur Taufiq; Sulthon Syahril Oku; Ryan Ari Setyawan (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2025)
Effective waste management is a significant challenge in efforts to create a sustainable environment. One crucial step in waste management is the recycling process, which requires an efficient and accurate sorting system. This study aims to implement Finite State Automata (FSA) as a modeling method to optimize the waste recycling process. FSA is used to model the waste sorting flow based on categories such as organic, inorganic, and hazardous materials. This model is designed to improve the speed and accuracy of identifying waste types suitable for recycling.